(untitled) - Miller, G. Tyler (Belmont, CA, 2007)
This is introduction about humans and sustainability, ecology and sustainability, sustaining biodiversity, sustaining key resource, sustaining environmental quality, sustaining human societies.
Keywords: Environmental sciences,Human ecology,Pollution,Sustainable development,Khoa học môi trường,Sinh thái học người